HUMAN RIGHTS IMPLICATIONS OF WSIS - Hamelink, Cees (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2005)
The author lists the references to human rights in the World Summit on the Information Society Declaration of Principles. He analyses the problems with these references on two levels. First, the references are made in a socio-political void without historical context. There are no proposals for concrete resource allocations for their implementation. Next, he raises the question of whether the second phase of the World Summit in November 2005 (in Tunis) can change this. The author states that, given present political and economic trends in the world, a fundamental change is not a realistic prospect. Even so, some proposals could be offered for possible human rights actions. Special attention is given to the need to assess the state of communication rights in the world and to further the discussion about the human right to communicate.